2021
DOI: 10.1186/s12903-021-01581-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two minimally invasive restorative techniques in improving the oral health-related quality of life of pregnant women: a six months randomized controlled trial

Abstract: Background Women tend to delay dental treatment due to misconceptions regarding the safety of dental procedures during pregnancy which may negatively affect their quality of life. Minimally invasive restorative techniques offer alternatives for caries treatment and can improve their oral health-related quality of life (OHRQoL) during this stage. Methods A randomized controlled clinical trial was conducted in 2019 and included 162 pregnant women vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Availability of alternative treatment options: A study carried out among pregnant women in Alexandria, Egypt with respondents having mild to moderate dental pain revealed that the choice of dental treatment among pregnant women were also influenced by the availability of alternative dental treatment options treatments which were major considerations in situations where significantly better alternatives existed over 75% of the participants who had less invasive treatments showed better oral health impact profile [20].…”
Section: Religious Beliefsmentioning
confidence: 99%
“…Availability of alternative treatment options: A study carried out among pregnant women in Alexandria, Egypt with respondents having mild to moderate dental pain revealed that the choice of dental treatment among pregnant women were also influenced by the availability of alternative dental treatment options treatments which were major considerations in situations where significantly better alternatives existed over 75% of the participants who had less invasive treatments showed better oral health impact profile [20].…”
Section: Religious Beliefsmentioning
confidence: 99%
“…Meanwhile, poor maternal oral health has been linked to an increased risk of dental caries in children [7] . Although routine oral care during pregnancy is safe [8] , many pregnant women delay dental treatment due to their misunderstanding of the safety of oral treatment during pregnancy [9] . Studies show that 66.6% − 70.1% of women visit a dentist during non-pregnancy [10] , while 16%-83% visit a dentist during pregnancy [11] .…”
Section: Introductionmentioning
confidence: 99%